DIABETIC CARDIOVASCULAR DISEASE: getting to the heart of the matter - Peterson, Linda R. (2012)
Diabetes is a major risk factor for heart disease, and heart disease is responsible for substantial morbidity and mortality among people living with diabetes. The diabetic metabolic milieu predisposes to aggressive obstructive coronary artery disease that causes heart attacks, heart failure and death. Furthermore, diabetes can be associated with heart failure, independent of underlying coronary artery disease, hypertension or valve abnormalities. The pathogenesis of the vascular and myocardial complications of diabetes is, as yet, incompletely understood. Although a number of medical and surgical approaches can improve outcomes in diabetic patients with cardiovascular disease, much remains to be learned in order to optimize approaches to these critical complications.